A massive degenerated uterine leiomyoma masquerading as an ovarian malignancy: a diagnostic dilemma - Negi, Ayushi; Varun, Neha; Tomar, Swati; Sharma, J. B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Leiomyoma of the uterus is the most common tumour of the female pelvis arising from the uterine smooth muscle. Large cystic degenerations and leiomyomas located in the adnexa can mimic ovarian malignancy and challenge the radiologist and the operating surgeon. We report here an unusual case of large cystic, degenerated uterine leiomyoma mimicking malignant ovarian tumour on imaging.